2004
DOI: 10.1002/ijc.20177
|View full text |Cite
|
Sign up to set email alerts
|

Targeting an extracellular epitope of the human multidrug resistance protein 1 (MRP1) in malignant cells with a novel recombinant single chain Fv antibody

Abstract: Inherent and acquired multidrug resistance (MDR) is characterized by a simultaneous resistance to diverse anticancer drugs and is a major impediment towards curative chemotherapy of cancer. Hence one important goal is to develop strategies aimed at specific targeting of major anticancer drug efflux transporters of the ATP-binding cassette (ABC) superfamily including multidrug resistance protein 1 -MRP1 (ABCC1). To date, no monoclonal antibody has been isolated that can target an extracellular MRP1 epitope. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The efforts of generating antibodies recognizing extracellular epitope(s) in ABCC1 and in other ABCC-like pumps were unsuccessful indicating that the extracellular loops and the extracellular amino-terminal segment of the ''long-ABCCs'' are relatively short and/or buried. However, recently, using a phage display approach, a recombinant single-chain Fv (scFv) antibody that specifically recognizes the extracellular N-terminal tail of the human ABCC1 has been developed [40].…”
Section: The Abcc-subfamilymentioning
confidence: 99%
“…The efforts of generating antibodies recognizing extracellular epitope(s) in ABCC1 and in other ABCC-like pumps were unsuccessful indicating that the extracellular loops and the extracellular amino-terminal segment of the ''long-ABCCs'' are relatively short and/or buried. However, recently, using a phage display approach, a recombinant single-chain Fv (scFv) antibody that specifically recognizes the extracellular N-terminal tail of the human ABCC1 has been developed [40].…”
Section: The Abcc-subfamilymentioning
confidence: 99%
“…The present study demonstrated the potential of MRP1 as a therapeutic target in the treatment of CRC with a MDR phenotype and will prompt efforts to develop agents that are able to repress MRP1-mediated drug transport. Currently, an antibody selective for MRP1 has been isolated; however, its specificity and efficiency as a chemosensitizer in the treatment of CRC has not yet been reported (17). Another potential treatment option is the post-transcriptional interference of MRP1 expression, as suggested by the results of the present study.…”
Section: Discussionmentioning
confidence: 69%
“…Maxisorb immunoplates were coated with biotinylated peptides (10 μg/ml) that were captured on BSA‐Biotin (10 μg/ml; Sigma, St. Louis, MO), streptavidin‐coated wells (10 μg/ml; Promega, Madison, WI) by an overnight incubation at 4°C. We used the MRP1‐derived peptide 1: M 1 ALRGFCSADGSDPLWDW,18 which was specifically targeted by the recombinant A5scFv antibody, and several other MRP1 or Pgp‐derived peptides, as described previously 12. Following blocking with 2% skim‐milk in PBS (Biological Industries, Beth‐Haemek, Israel), the purified A5scFv‐PE38 immunotoxin (in sequential dilutions) was added for 1 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…We further showed that one of these recombinant antibodies (termed A2scFV) abolished the drug efflux activity of Pgp and thereby reversed the MDR phenotype of human carcinoma cells to doxorubicin 11. Extending on these studies, we recently isolated another recombinant scFv antibody (termed A5scFV) that specifically targets an extracellular N‐terminal epitope of the human MRP1 as expressed on the surface of viable tumor cells with MRP1 overexpression 12. In an attempt specifically to target and eradicate MDR malignant cells with MRP1 overexpression, we fused the A5scFv antibody to Pseudomonas exotoxin.…”
mentioning
confidence: 99%